1964
DOI: 10.1126/science.145.3632.602
|View full text |Cite
|
Sign up to set email alerts
|

Behavior in Hydra : Inhibition of the Contraction Responses of Hydra pirardi

Abstract: Hydra pirardi contracts spontaneously and in response to external stimuli of light and mechanical agitation. Inhibition of these contractions occurs when the animal feeds on Artemia salina or when reduced glutathione is present in the environment. Such inhibition demonstrates the control of one receptor-effector system by another in hydra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1967
1967
1981
1981

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…That is, in the early trials, failure to respond is due to Artemiainduced suppression, while in the later trials responding may have habituated with repeated stimulation. Rushforth et al (1964) report no interaction between habituation and Artemia-induced suppression; however, previous reports have established that habituation occurs in Hydra only after several hours of mechanical stimulation.…”
Section: Discussionmentioning
confidence: 64%
“…That is, in the early trials, failure to respond is due to Artemiainduced suppression, while in the later trials responding may have habituated with repeated stimulation. Rushforth et al (1964) report no interaction between habituation and Artemia-induced suppression; however, previous reports have established that habituation occurs in Hydra only after several hours of mechanical stimulation.…”
Section: Discussionmentioning
confidence: 64%
“…Earlier observations with H. pirardi show that contractions induced by shaking are suppressed when the animal feeds on Artemia salina or is exposed to extracts of Artemia. Inhibition is also observed when GSH is present in the environment of the animal (Rushforth et al, 1964). In H. viridis marked inhibition of mechanically induced contractions occurs with 10 -5 M GSH.…”
Section: Effects Of Chemical Stimulation On the Sensitivity Of Hydra mentioning
confidence: 98%
“…The weight of evidence regarding the specificity of the hydra receptor for glutathione was increased when Rushforth et al (17) showed that the same conformation of glutathione plays another unique role, that of regulating two other receptor-effector systems in hydra, as discussed below.…”
mentioning
confidence: 99%
“…Rushforth (17,31) has been conducting extensive and convincing experiments which show that the contractions of hydra induced either by light or by shaking, as well as the animals' spontaneous contractions, are inhibited while the animals are feeding on Artemia salina. Prompted by the experiments on the feeding response, Rushforth tested, first, Artemia extracts and then reduced glutathione; both inhibited the contractions.…”
mentioning
confidence: 99%